The Real, the Imaginary, and Childhood Anxiety in Neil Gaiman's Coraline A Lacanian Psychoanalytic Analysis - Sri Saraswati; Yudhanita Pratiwi; Arroyo Estrelle, T. (Pujangga, 2026)
This study examines the representation of childhood anxiety in Neil Gaiman's Coraline through the lens of Jacques Lacan's psychoanalytic theory. Drawing upon Lacan's triadic model of the Imaginary, the Symbolic, and the Real, the research explores how Coraline's journey through the alternate world reflects a process of psychological maturation and subject formation. Employing qualitative textual analysis, the study investigates the relationship between fantasy, desire, anxiety, and identity construction in the novel. The findings reveal that the alternate world functions as the Imaginary Order, offering an illusion of completeness and fulfillment that initially satisfies Coraline's desires. The Other Mother embodies the fantasy of perfect maternal care while simultaneously concealing a predatory desire for possession and control. As Coraline uncovers the hidden truths of the alternate world, she encounters manifestations of the Real that disrupt the coherence of fantasy and generate anxiety. These encounters force Coraline to confront the limitations of desire and the impossibility of complete satisfaction. Ultimately, the novel portrays anxiety not as a destructive force but as a necessary condition for psychological growth. Through her confrontation with the Real, Coraline develops a more mature understanding of herself and her relationship to reality. This study contributes to children's literature scholarship by demonstrating how Lacanian psychoanalysis provides valuable insights into the psychological dimensions of fantasy narratives and the role of anxiety in childhood development.